Studying the Effects of Tuber Size and Spacing between Plants on Growth and Yield of Potato (Solanum tuberosum L.) - Saifullah, Mangal; Hakimullah, Abid; Khan, Bihroz Moula; Mudir, Atif (Journal for Research in Applied Sciences and Biotechnology, 2024)
A field experiment was carried out to investigate the impact of different plant spacings and tuber sizes on the growth and yield of potatoes (Solanum tuberosum L.). Four tuber sizes (10-20 g, 20-30 g, 30-40 g, and 40-50 g) and three plant spacings (60 x 15 cm, 60 x 30 cm, and 60 x 45 cm) were examined. The study found significant effects of both plant spacing and tuber size on various growth and yield parameters. Increasing plant spacing generally led to increased shoot growth and tuber weight per plant but decreased plant height and overall tuber yield. Similarly, larger tuber sizes were associated with higher emergence rates and yields. The 'Desiree' potato variety showed the highest total tuber yield (62.363 t/ha) when planted with 40–50 g tubers at a spacing of 60 x 15 cm, followed by a yield of 41.136 t/ha with 30–40 g tubers at a spacing of 60 x 30 cm. Optimal production was achieved with a spacing of 60 x 15 cm, and using 40–50 g tubers resulted in the highest yield.